The consequences of swim, cycle, and run performance on overall result in elite Olympic distance triathlon - Vleck, V. E.; Bürgi, A.; Bentley, D. J. (International Journal of Sports Medicine, 2006)
This study examined the consequences of performance in swim, cycle, and run phases on overall race finish in an elite "draft legal" Olympic distance (OD) triathlon. The subjects were 24 male athletes grouped by rank order into the top 50 % (n = 12) and bottom 50 % (n = 12) of the race population. Swimming velocity (m · s-1), cycling speed (km · h-1), and running velocity (m · s-1) were measured at regular intervals using a global positioning system, chip timing system, and video analysis. Actual rank after each stage and overall was obtained from the race results and video analysis. The top 50 % athletes overall swam faster over the first 400 m of the swim phase (p > 0.05). Their swim ranking was lower (p < 0.01) than the bottom 50 % athletes after this stage. There were no significant differences in actual race position between the groups after the cycle. However, the bottom 50 % athletes after the swim stage cycled faster (p < 0.01) at 13.4 km of the cycle. Speed at 13.4 km of the cycle stage was inversely correlated (r = 0.60, p < 0.01) to running performance. Performance (rank and velocity) in the running stage was highly correlated with overall race result (r = 0.86 and - 0.53, respectively, both p > 0.01). It appears that inferior swimming performance can result in a tactic that involves greater work in the initial stages of the cycle stage of elite OD racing, and may influence subsequent running performance.